From the synthesis of hBN crystals to their use as nanosheets in van der Waals heterostructures. (1st July 2022) - Maestre, Camille; Li, Yangdi; Garnier, Vincent; Steyer, Philippe; Roux, Sébastien; Plaud, Alexandre; Loiseau, Annick; Barjon, Julien; Ren, Lei; Robert, Cedric; Han, Bo; Marie, Xavier; et al.
Abstract: In the wide world of 2D materials, hexagonal boron nitride (hBN) holds a special place due to its excellent characteristics. In addition to its thermal, chemical and mechanical stability, hBN demonstrates high thermal conductivity, low compressibility, and wide band gap around 6 eV, making it a promising candidate for many groundbreaking applications and more specifically in van der Waals heterostructures. Millimeters scale hBN crystals are obtained through a disruptive dual method (polymer derived ceramics (PDC)/pressure-controlled sintering (PCS)) consisting in a complementary coupling of the PDC route and a PCS process. In addition to their excellent chemical and crystalline quality, these crystals exhibit a free exciton lifetime of 0.43 ns, as determined by time-resolved cathodoluminescence measurements, confirming their interesting optical properties. To go further in applicative fields, hBN crystals are then exfoliated, and resulting boron nitride nanosheets (BNNSs) are used to encapsulate transition metal dichalcogenides (TMDs). Such van der Waals heterostructures are tested by optical spectroscopy. BNNSs do not luminesce in the emission spectral range of TMDs and the photoluminescence width of the exciton at 4 K is in the range 2–3 meV. All these results demonstrate that these BNNSs are of high quality and relevant for future opto-electronic applications.